A case study of spun pile / Fatimah Atifah Seyed Mohamed Mohamed Nazim - Seyed Mohamed Mohamed Nazim, Fatimah Atifah (Universiti Teknologi MARA, Perak, 2019)
Substructure is an important part in construction process, therefore this report will discuss about piling work which are an important structure below ground. Piling work is defined as one of deep foundation used to transfer the load to a deeper level using vertical column made of concrete, steel or wood. The function of piling is to give extra support to the building that sits on top. This report will focus on all the works related to piling and all the machines and equipment used. This report will also look at the type of pile load test applied on the piles as the method and equipment are describe in detail. Piling might be the only part that cannot be seen in a building but it plays a big role on the building structure as all load are transferred to it, a strong piling is indeed a must.